FEATURES OF THE PROCESS OF SOCIALIZATION IN PRESCHOOL AGE - Tleumbetova Kalligul Dilimbetovna; Seitmuratova Venera Jumamuratovna (Galaxy International Interdisciplinary Research Journal, 2021)
The article examines the features of the process of socialization in preschool age, because preschool age is sensitive for the formation of social experiences in children, and also an indicator of successful socialization is a positive emotional attitude to the values and standards transmitted to adults.